Novel Arithmetic Equations for Mass Energy Equivalence, Newton’s Rings Radius, Wavelength and Speed of Light, Fine Structure Constant and Ideal Gas Law Correlated with eπ Based on Sayed’s Theorem (JOURNAL OF ADVANCES IN PHYSICS, 2022)
Many proved scientific facts are mentioned in the generous Quran. This article introduces revisiting, revising and rewriting of well-established equations and laws of different applied fields of science and engineering. The eπ has been correlated with the mass energy equation of special relativity, fine structure constant, Newton`s rings radius, light wavelength, speed of light and ideal gas law. The correlated formulas were achieved based on the published Sayed`s equations and theorem. The fine structure constant was calculated and compared with a published value with 8.6435x10-5 discrepancy percentage. The novel deduced equations/formulas can be considered as confident mathematical expressions to be parallel used in the abovementioned and other scientific fields.